Erythrodiplax ana sp. nov. (Odonata: Libellulidae) from Brazilian palm swamps - Guillermo-Ferreira, Rhainer; Vilela, Diogo S.; Del-Claro, Kleber; Bispo, Pitágoras C. [UNESP] (Magnolia Press, 2016)
Erythrodiplax ana sp. nov. (male holotype, six male and three female paratypes), collected in Vereda wetlands (a unique Neotropical savanna environment) in Uberlândia (Minas Gerais) and Chapada dos Guimarães (Mato Grosso), Brazil, is described and illustrated. The new species fits in Borror's Basalis Group, and can be distinguished from other species by the combination of the following traits: blue pruinosity dorsally on thorax and third to eighth abdominal segments; sides of the thorax olive-green; face ivory or olive-green; wings hyaline with a small apical brown spot on all four wings, well defined in females; male genitalia with sclerotized erectile posterior lobe and inflatable sac-like median process. Last instar larvae were reared in the laboratory, resulting in the description of the larva. We also followed this population for 13 months and present resulting biological notes and comments on ontogenetic color change in males, as well as longevity.
Keywords: Brazil; Cerrado; Dragonfly; New species; Taxonomy